UJI EFEKTIVITAS EKSTRAK LENGKUAS MERAH (Alpinapurpurata K.Schum) DALAM MENGHAMBAT PERTUMBUHAN BAKTERI Eschericia coli SECARA IN VITRO - Fioni Fioni (Universitas Prima Indonesia, 2021)
Red ginger with the Latin name Alpina purpurata K. Schum is a plant of the family zingiberaceae (family ginger family) which has several medical benefits. Zingiberaceous has about 50 genera and 1300 species spread throughout the world. In relation to the flavonoid content, routine, kaempferol-3-rutionoside and kaemferol-3-oliucronide in red ginger (Alpina purpurata K. Schum) as antimicrobial, then to prove this, the trials of antimicrobial efficacy in vitro by diffusion disc (method Kirby & Bauer test) against Escherichia coli which is a gram negative bacteria. The results were analyzed with SPSS 20 software. The results showed that red ginger extract (Alpina purpurata K. Schum) effective in the course of Escherichia coli growth was at 100% concentration. The mean inhibition zone diameter was 7.825 mm at 25%, 8,625 mm at concentration 50%, 9,350 mm at concentration 75%, and 10.7 mm at 100% concentration.